Central Retinal Vein Occlusion Associated With Progestin-Only Contraceptive Implant Use - Jan Patrick O. Chu; David I. T. Sia (Case Reports in Ophthalmological Medicine)
Conclusion: This study recognized that the use of progestin-only contraceptives still has an increased risk of thrombosis. It is essential to consider the mode of administration and duration of use of these contraceptives.